Personal photograph collections ontology development through thematic tags - Manoli, Vasiliki; Triantafyllou, Ioannis (Journal of Integrated Information Management, 2024)
Purpose - The number and the variety of photos have grown to a great extent as they can be created anytime, everywhere and spontaneously. Searching for a particular photo file has become a boring, repetitive and tedious activity. The application of an ontology to express the user profile characteristics relation with the narrative, spatial, time and other types of information of the collected photos becomes imperative. Design/methodology/approach -The work presented in our article includes the development of a personal photograph collections ontology (MyOntoPhotos) specialising in documenting the metadata of the topics that end-users prefer mostly to capture with their devices. An extensive survey, among 650 participants, was conducted with the use of an online questionnaire comprised of semi-closed questions, following the Likert scale and the scale category grading. Findings -The ontology created was based on the results of an extensive survey aiming to identify thematic areas of interest, apart from spatial and temporal information, as other similar efforts did in the past. It is mentionable that the survey results proved the majority of the responders selected 22 thematic tags. Originality/value -Based on the research findings an innovative concept for a mobile application is presented, focusing on enhancing end-users photo collections organizing and retrieval functions.